Influence of Butylated Hydroxyanisole on the Growth, Hyphal Morphology, and the Biosynthesis of Fumonisins in Fusarium proliferatum - Li, Taotao; Jian, Qijie; Chen, Feng; Wang, Yong; Gong, Liang; Duan, Xuewu; Yang, Bao; Jiang, Yueming (Frontiers in Microbiology, 2016)
Fusarium proliferatum as a common fungus pathogen in foods can produce toxic fumonisins, which can cause animal diseases and increase risks of human cancers. On contrary, butylated hydroxyanisole (BHA) as a synthetic antioxidant offers a clue for preventing growth of fungal species and inhibiting production of mycotoxins. Unfortunately, information of the inhibitory mechanism of BHA on Fusarium species is still limited. In this study, influence of BHA treatment on growth and inhibition of fumonisin production in relation to the expression of the fumonisin biosynthesis-related genes of the F. proliferatum ZYF was investigated, which revealed that BHA had a negative influence on growth and fumonisin production of F. proliferatum. To further elucidate the mechanism of BHA on the growth of F. proliferatum, scanning electron microscopy (SEM) and transmission electron microscopy (TEM) were used to examine the F. proliferatum hyphae. The BHA treatment induced the loss of cytoplasm and cellular constituents, as well as distortion of mycelia, but it did not directly degrade the fumonisin. Furthermore, the BHA treatment markedly inhibited the expressions of FUM1 (a polyketide synthase encoding gene) and FUM8 (an aminotransferase encoding gene) genes, which resulted in the depression of metabolic pathway of F. proliferatum. The transcriptional analyses of the FUM1 and FUM8 genes confirmed a correlation between the fumonisin production and its gene expression. This study provided some insights into mechanisms of production of fumonisin and feasible prevention to reduce fumonisin contamination in favor of human and animal health.